Mental Budgeting dan Motivasi Terhadap Pengelolaan Keuangan Individu - Eka Rosalina; Rida Rahim; Tafdil Husni; Fany Alfarisi (Journal of Applied Accounting and Taxation, 2021)
Budgeting cannot be separated from personality and by itself arises from the human individual—people who will make and run the budget. With the budget, financial management will be better. This research was conducted to find out the influence of mental budgeting and motivation on the financial management of individuals. This research was conducted through a questionnaire survey distributed to polytechnic students in 2021 who had taken budget and financial management courses. The sample from this study was 108 samples using Slovin and random sampling techniques. It was then continued with hypothesis testing using multiple linear regressions. The results of this study state that mental budgeting has a positive effect on individuals' financial management, and motivations positively affect personal financial management.